Selective Import: French Feminist Theory and Anglophone Critical Discourses - Adamczewski, Tymon (Romanica Silesiana)
The article aims to sketch the reception and the representations of French feminist discourses in the Anglo-American critical theory starting from the early 1970s. It situates French Feminism within the field of French Theory, a notion created in the Anglophone critical discourses, and analyses the meanings ascribed to both terms. Through a historicised discussion of the appropriation of the French theories — for a long time limited to the propositions of Julia Kristeva, Hélène Cixous and Luce Irigaray — the text also attempts to present the popular critical moves (selectiveness and standardisation) in this process. What follows constitutes a brief analysis of the reasons and responses to the propagation of French feminism as a reductive construct. The article concludes registering a change in more contemporary approaches which attempt to move beyond the initial label. Key words: French Theory, French feminism, theoretical discourse, poststructuralism.